Electrophysiological and behavioral responses of Tomicus minor (Coleoptera: Scolytidae) to host volatiles - Hua, Yang; Hong-Wei, Wang; Wei, Yang; Chun-Ping, Yang (Entomologica Fennica, 2015)
To screen for host volatiles that effectively attract the lesser pine shoot beetle, Tomicus minor (Coleoptera: Scolytidae), an important forest pest, water vapor distillation extraction and gas chromatography-mass spectrometry were combined to analyze volatiles emitted from uninfested and infested shoots of Pinus yunnanensis (Pinaceae). Electroantennography and Y-tube olfactometer behavioral tests were used to compare and analyze the responses of male and female beetles to each of selected eight compounds. The spectrometry results showed that monoterpenes are the primary chemicals emitted by P. yunnanensis. The electroantennogram responses of adult T. minor to six of the plant compounds peaked at 10 μg/μL; the exceptions were terpinolene and myrcene, which had maxima above 100 μg/μL. (+)-α-Pinene and β-phellandrene were strongly attractiveto the male and female adults.